Ultrathin Spin-Decoupled Meta-Devices for Independent Control of Electromagnetic Waves With Dual-Orthogonal Circular Polarization - Chen, Wenqiong; Qi, Buxiong; Zhang, Jingwei; Niu, Tiaoming; Mei, Zhonglei (Frontiers in Materials, 2021)
Inspired by the concept of miniaturized and integrated systems, an ultrathin and multifunctional metasurface device is highly desirable in microwave fields. It is an inherent characteristic that the two spin phase states of electromagnetic waves imparted by the geometric phase are always conjugate symmetric, i.e., the geometric phase produces anti-symmetrical phase responses between dual-orthogonal circular polarization states. So it is extremely crucial to break the conjugate constraints and realize the completely independent control of electromagnetic waves with dual-orthogonal circular polarization. Based on this perspective, ultrathin and bifunctional meta-devices operating in reflection mode are proposed to independently manipulate the left-handed and right-handed circularly polarized waves, which are constructed by anisotropic meta-atoms with synthetical geometric and propagation phases. It is worth noting that the component elements only need a single-layer structure with the thickness of 0.07λ0. Several design samples are presented to achieve functionalities of beam focusing, vortex wave generation, and beam deflection, respectively. Experiments are performed and show good consistence with the simulation results, successfully verifying the performance of the designed metasurfaces. The research results in this paper pave the way to design low-profile and bifunctional devices with independent controls of circularly polarized waves, which is expected to expand the working capacity of metasurfaces to realize complex electromagnetic wave manipulation with a new degree of freedom.